CLUES about M33: the reversed radial stellar age gradient in the outskirts of Triangulum galaxy. Issue 4 (8th August 2018) - Mostoghiu, Robert; Di Cintio, Arianna; Knebe, Alexander; Libeskind, Noam I; Minchev, Ivan; Brook, Chris
ABSTRACT: HST /ACS observations along the major axis of M33 show that the mean age of its stars decreases with increasing distance from the galaxy centre. Such a behaviour is consistent with an inside-out growth of the disc. However, in the outermost observed field, at r ≃ 11.6 kpc, a reversal of this gradient is detected, with old stars found in high percentages beyond this radius. In this work, we investigate the origin of such a reversal in stellar age gradient, by using a simulated M33 analogue from the Constrained Local UniversE Simulations (CLUES). The simulated M33 is similar to the observed one in terms of mass, rotation velocity, surface brightness, and, similar to what has been reported in observations, shows a stellar age turnaround at large radii. We demonstrate that this reversal is mostly a result of stellar accretion from old satellite galaxies and, to a lesser extent, of stellar migration of in-situ stars. The old accreted stars, with formation times tf < 4 Gyrs, are kinematically hot and can be differentiated from the in-situ stars by their high velocity dispersion and the fact that they do not have rotationally supported orbits. In the future, obtaining kinematic information of the stars in the outskirt of M33 will help to verify this scenario.